Keterlibatan Organisasi Kriminal Transnasional Dalam Jaringan Perdagangan Manusia - Ilmih, Andi Aina; Arabel, Yunita Sekar Ety (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Human trafficking involving transnational criminal organizations is a serious problem that requires global attention. This research investigates the modus operandi, strategies, and impact of transnational criminal organizations' involvement in human trafficking, as well as the effectiveness of law enforcement and victim protection efforts. Research methods use qualitative and quantitative approaches, including case studies, interviews, document analysis, and surveys. The results highlight the complexity of this phenomenon, the importance of cross-national cooperation, and the detrimental impact on victims. In conclusion, joint efforts from governments, law enforcement agencies, NGOs and civil society are needed to overcome these challenges. Solidarity between nations is key in fighting transnational criminal organizations, underscoring the need for a collective response to protect human rights and ensure global peace.